THE METHODS HELPING TO IMPROVE READING SKILL (Multidisciplinary Journal of Science and Technology, 2024)
Reading is a vital ability required for academic achievement and lifetime learning. This article looks at many methods for efficiently improving learners' reading skills. By analyzing current literature and incorporating empirical findings, the study identifies essential techniques such as phonics instruction, vocabulary development, reading comprehension tactics, and the use of technology. The findings emphasize the necessity of a varied approach to reading education that is adapted to the needs of individual students.